Prawo i Sprawiedliwość w polskim systemie partyjnym (przyczynek do dyskusji o systemotwórczej roli partii) - Antoszewski, Andrzej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
Among the numerous functions of political parties, the role of creating the governance system is highly significant. It manifests itself in the ability of political parties to establish permanent relations with the other parties and in this way provides the essence of a party system. The purpose of the present paper is to demonstrate the role the Law and Justice party (PiS) plays in the creation of the governance system. Since 2005, PiS has been one of the two dominant political parties struggling to win the parliamentary and presidential elections. In order to determine the scope of this party’s influence on the shape of the party system, their achievements in elections, parliament and Cabinet activity need to be analyzed. Such a quantitative analysis allows us to grasp PiS’s development trends in political competition. The paper discusses the reasons for their electoral success in 2005 as well as their defeat in 2007 and the aftermath of both these elections for the party’s competition to the government. The achievements of PiS confirm that this party has won the status of a party that structures the political competition, a status that has not been lost irrespective of the five elections at different levels that the party has lost. PiS has successfully adopted the postulates of the Left in terms of the economy and social issues, whereas it has maintained the image of a right-wing party in terms of the shape of the state and its moral foundations. PiS has managed to form an electorate that differs from other parties’ electorates in terms of its social and demographic properties as well as its political attitudes, which reinforces the position of PiS in the electoral struggle. Yet PiS has failed to establish a permanent coalition government. The elimination of Self-Defence (Samoobrona) and the League of Polish Families (LPR) from the Sejm has practically deprived PiS of any coalition potential, or has at least significantly reduced this potential. This, coupled with a continuously growing negative electorate, may turn out to constitute the main obstacle to PiS regaining power.